Pemasaran Islami: Mengoptimalkan Potensi Pasar dengan Prinsip Keadilan dan Etika Ekonomi Islam - Istiqomah, Nur Hidayatul; Nisa’, Ihda Shofiyatun; Husniyah, Latifatul (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2024)
This study aims to investigate the concept of Islamic marketing and how its implementation can optimize market potential with principles of justice and Islamic economic ethics. Business ethics in Islamic marketing involve adherence to moral principles and religious values, while justice ensures fair treatment for all parties involved. In the context of Islamic marketing, companies are expected to maintain integrity, avoid practices that are inconsistent with Islamic teachings, and ensure fair pricing and value of products or services offered. Ethical values in Islamic marketing include honesty and accuracy in conveying information to consumers, while avoiding deceptive promotions or violations of Sharia principles. Islamic marketing also reflects a company's commitment to religious values and contributes to sustainable economic growth. This research provides insights into the importance of Islamic marketing in optimizing market potential with principles of justice and Islamic economic ethics, and provides a foundation for companies to develop marketing strategies aligned with Islamic values in order to achieve sustainable business goals.